(untitled) (Romanian Studies Today, 2024)
The present work represents a part of our research-concerns in recent years and will focus on the main theoretical aspects of the phenomenon of linguistic „habituation” (according to the famous Heideggerian phrase "language is the home of being") and the phenomenon of migration, in an attempt to integrate them in two perspectives: a sociological-philosophical one and a linguistic one. Therefore, we will try to underline and to find answers to some questions related to the essence of the migratory phenomenon in today’s globalizing society, proposing, mainly, to identify what are its effects on the linguistic behavior of people who migrate, how it modifies the main coordinates of living in a language (abandonment of the mother tongue and installation in a new linguistic reality different from the mother tongue’s one).